Use of a Mouse Model of Pancreatic Neuroendocrine Tumors to Find Pericyte Biomarkers of Resistance to Anti-angiogenic Therapy - Franco, M.; Pàez-Ribes, M.; Cortez, E.; Casanovas, O.; Pietras, K. (Hormone and Metabolic Research, 2011)
The successful introduction of rationally targeted agents into standard cancer care is a testimony of the vast knowledge base in tumor biology. However, in order to provide individually tailored therapy to patients and to identify small subsets of patients with a high likelihood to benefit from treatment, the identification of biomarkers for response or resistance to a particular therapeutic regimen is imperative. Herein, by the use of a genetically engineered mouse model of pancreatic neuroendocrine tumors, we have assessed the utility of pericyte characteristics in terms of differential marker expression to serve as surrogate markers for response or evasive resistance to anti-angiogenic therapy. We found that tumors refractory to therapy following long-term treatment with a vascular endothelial growth factor receptor-2 blocking antibody contained blood vessels with a prolific investment of pericytes expressing α-smooth muscle actin. Further analysis by simultaneous immunostaining for different pericyte markers led to the conclusion that the increased abundance of this particular subtype of blood vessels most likely occurred by co-option of vessels from the surrounding exocrine pancreas. Our findings may form the basis for retrospective analysis of pancreatic neuroendocrine tumors from patients having undergone treatment with anti-angiogenic agents in order to validate the occurrence of pericytes expressing α-smooth muscle actin as a biomarker for tumors refractory to therapy.
Keywords: angiogenesis; targeted therapy; mouse models of cancer; therapeutic resistance